Avalanches during flexure of early-age steel fiber reinforced concrete beams - Liu, Zhuang; Worley, Robert; Du, Fen; Giles, Courtney D.; Dewoolkar, Mandar; Huston, Dryver; Tan, Ting (Materials and structures, 2020)
In this work, we studied stress variations occurring during flexure of early-age steel fiber reinforced concrete beams. By preparing beams with different fiber volume ratios, four-point bending tests were performed to evaluate the specimens at different loading rates. A new experimental system was created to collect the stress-time curves collected at 100 kHz sampling rate so that temporal profiles of stress drops were analyzed in high resolution. Meanwhile, stress drops were modeled as avalanches due to interactions between steel fibers and cement matrices during flexure. Good agreement on avalanche statistics and dynamics was obtained between measurements and the predicted power law exponents and scaling functions from the mean field model. The observations of different avalanche types also illustrated the essential failure features evolved during flexure of steel fiber reinforced beams.